Practice of European Сourt in the field of defence of human rights in relation to the crimes of torture - Замула, Аліна Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Creation of the effective system of protection of human rights and its efficiency is analysed in relation to the crime of «torture» in the context of European Convention on human rights, which must be in future stored and taken for basis for a further improvement and systematization of the single European standards in area of human rights